2019
DOI: 10.1159/000499325
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Ectodermal Dysplasia Cohort: From Phenotype to Genotype in 17 Families

Abstract: Hypohidrotic or anhidrotic ectodermal dysplasia (HED/EDA) is characterized by impaired development of the hair, teeth, or sweat glands. HED/EDA is inherited in an X-linked, autosomal dominant, or autosomal recessive pattern and caused by the pathogenic variants in 4 genes: EDA, EDAR, EDARADD, and WNT10A. The aim of the present study was to perform molecular screening of these 4 genes in a cohort of Turkish individuals diagnosed with HED/EDA. We screened for pathogenic variants of WNT10A, EDA, EDAR, and EDARADD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
1
7
1
1
Order By: Relevance
“…More than half of these variants are localized to exons 1, 3 and 5. This report supports the observation that patients with EDA mutations are more likely to exhibit the characteristic XLHED triad of hypodontia, anhidrosis/hypohidrosis and hypotricosis 4,12 as opposed to patients with isolated microdontia and lack of facial dysmorphism, who are more likely to harbour WNT10A mutations 4 …”
Section: Application Predictionsupporting
confidence: 88%
“…More than half of these variants are localized to exons 1, 3 and 5. This report supports the observation that patients with EDA mutations are more likely to exhibit the characteristic XLHED triad of hypodontia, anhidrosis/hypohidrosis and hypotricosis 4,12 as opposed to patients with isolated microdontia and lack of facial dysmorphism, who are more likely to harbour WNT10A mutations 4 …”
Section: Application Predictionsupporting
confidence: 88%
“…The weighted average of nine articles evaluating males was 83.6% with sparse hair, 11.8% with alopecia, and 88.1% with any degree of reduced hair. Cluzeau et al (2011) and Güven et al () both reported data for hypotrichosis categorically and thus could not be included in the data for males. Cluzeau et al (2011) categorized hypotrichosis by severity as no effect, mild, moderate, or severe but did not explain the criteria for these categories.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 males, 100% had some degree of hypotrichosis: 9 had mild, 13 had moderate, and 7 had severe. Güven et al () categorized hypotrichosis using plus signs; the more plus signs the higher the severity. Of the 6 males, all had some degree of hypotrichosis as well, with 3 having one plus sign and 3 having two.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations